Malaysia's Gastrodiplomacy Strategy in Promoting Halal Friendly Country for Global Muslim Tourists in 2023 - Zulfia S; Kaslam, Kaslam; Muhammad Saleh Tajuddin (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
This study investigates how halal culinary branding and gastrodiplomacy contribute to national identity formation, tourism competitiveness, and international diplomacy, with a focus on Malaysia as a leading case in 2023. The research aims to evaluate how Islamic principles are embedded within national tourism strategies and how culinary initiatives shape perceptions and promote intercultural engagement. Using a qualitative descriptive-analytical approach, the study integrates document analysis of policy frameworks, literature on soft power and religious diplomacy, and secondary data from halal tourism campaigns, certification systems, and branding practices. The findings reveal that halal certification, when aligned with ethical stewardship and nation branding, significantly enhances trust among Muslim travelers and positions Malaysia favorably in global tourism indices. Culinary diplomacy events and digital influencer engagement serve as powerful platforms for promoting national identity, while halal standards offer robust indicators of food safety and cultural integrity. The study concludes that integrating religious values with culinary diplomacy strategies not only elevates national image but also promotes economic growth and cross-cultural understanding. These findings offer critical insights into the development of inclusive, ethically grounded, and sustainable Islamic tourism policies.